RETRACTED: Mechanisms Contributing to the Generation of Mayer Waves - Ghali, Michael G. Z.; Ghali, George Z. (Frontiers in Neuroscience, 2020)
Mayer waves were initially observed in 1876 by Sir Sigmund Mayer in anesthetized rabbits, describing oscillations with a lesser frequency compared with respirophasic variations described a few years earlier by Traube in 1865 and Hering in 1869. The origins of Mayer waves remains a mystery. The works of Guyton, Harris, and Andersson in the 1950’s seemed to support baroreflex or chemoreflex mechanisms as principally generative of these oscillations. Later authors demonstrated spectral power reduction, though persistence, of Mayer waves following sinoaortic denervation or pharmacological ganglionic antagonism, in most experiments, indicating supraspinal and/or spinal microcircuits oscillators may generate this rhythmic activity. Candidate zones chiefly generating these oscillations include the medullary lateral tegmental field and rostral ventrolateral medulla, though our impression leads us to strongly believe these oscillations may represent a general rhythm expressed by most neurons. Authors would later indicate persistence of these oscillations following cervicomedullary transection, providing evidence indicating the spinal cord may be capable of generating Mayer waves. Intra-neuraxially generated Mayer waves propagate throughout propriospinal interneurons constituting brainstem and spinal cord microcircuits oscillators and are conveyed via sympathetic nerves to sympathetically innervated arterioles, becoming manifest in arterial pressure, peripheral resistance, and blood flow. We propose arteriogenic oscillations propagating through the neural interstitium generate oscillations of neuronal membranes and neuronal biophysical properties leading to oscillations of electronically propagated graded somatodendritic potentials and neuronal spiking behavior. Out-of-phase summation of arteriogenic very low frequency oscillations may generate integer pseudo-harmonic Mayer waves.